2009
DOI: 10.1158/1078-0432.ccr-09-1438
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic Reaction to Colorectal Cancer Is Associated with Longer Survival, Independent of Lymph Node Count, Microsatellite Instability, and CpG Island Methylator Phenotype

Abstract: Purpose: Host immune response to tumor may be an important prognostic factor for colon cancer patients. However, little is known on prognostic significance of histopathologic lymphoid reaction to tumor, independent of the number of lymph nodes examined and tumoral molecular alterations, including microsatellite instability (MSI) and the CpG island methylator phenotype (CIMP), both of which are associated with lymphocytic reaction and clinical outcome. Experimental Design: Using 843 colorectal cancer patients i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

25
393
1
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 377 publications
(423 citation statements)
references
References 48 publications
25
393
1
4
Order By: Relevance
“…[24][25][26][27][28][29][30][31][32][33] As in this study, MSI tumors have previously been reported to have a higher degree of T-cell infiltration than MSS tumors. [35][36][37] Yet the potential confounding effect of MSI screening status on the prognostic importance of T-cell infiltration has been considered in only a minority of reports, of which most, 32,36,[39][40][41]46,53,54 but not all, 30,55 found that the better prognosis associated with dense T-cell infiltration was independent of MSI screening status. In this study, a better prognosis was seen in patients with MSS tumors densely infiltrated by T cells compared with poorly or intermediately infiltrated MSI tumors, whereas MSI screening status was not significantly related to prognosis in subgroups of highly and poorly infiltrated tumors separately.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…[24][25][26][27][28][29][30][31][32][33] As in this study, MSI tumors have previously been reported to have a higher degree of T-cell infiltration than MSS tumors. [35][36][37] Yet the potential confounding effect of MSI screening status on the prognostic importance of T-cell infiltration has been considered in only a minority of reports, of which most, 32,36,[39][40][41]46,53,54 but not all, 30,55 found that the better prognosis associated with dense T-cell infiltration was independent of MSI screening status. In this study, a better prognosis was seen in patients with MSS tumors densely infiltrated by T cells compared with poorly or intermediately infiltrated MSI tumors, whereas MSI screening status was not significantly related to prognosis in subgroups of highly and poorly infiltrated tumors separately.…”
Section: Discussionsupporting
confidence: 61%
“…Presence of peri-and intratumoral inflammatory cells has consistently been associated with a better prognosis in colorectal cancer. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Many of these reports have been based on routine hematoxylin and eosin stained tissue sections, but an increasing number of studies have used immunohistochemical markers such as the pan T-cell marker CD3. CD3 is a cell surface protein associated with the T-cell receptor.…”
mentioning
confidence: 99%
See 3 more Smart Citations